Recurrent Pancreatitis Associated with CFTR Heterozygous Mutation - Yıldız, Tuğçe Şevval; Şenocak, Şeyma (Archives of Case Reports, 2025)
This case report discusses a 74-year-old male patient diagnosed with recurrent pancreatitis associated with a CFTR heterozygous mutation. The patient presented with complaints of epigastric pain, and laboratory findings revealed elevated amylase and lipase levelsGenetic testing revealed a p.Phe1052Val (c.3154T>G) heterozygous mutation in the CFTR gene, which has been associated with recurrent pancreatitis through autosomal dominant inheritance. A cystic lesion detected in the pancreas (suggestive of IPMN or serous cystic neoplasm) was evaluated for malignancy and deemed low-risk based on PET-CT findings and a negative CA 19-9 level. This case is presented to emphasize that CFTR mutations should be considered in the differential diagnosis of patients with recurrent pancreatitis, that symptoms may present in adulthood, and that the diagnosis can be easily established through genetic testing.